2005
DOI: 10.1016/j.atmosenv.2004.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Wet and dry season ecosystem level fluxes of isoprene and monoterpenes from a southeast Asian secondary forest and rubber tree plantation

Abstract: Canopy scale fluxes of isoprene and monoterpenes were investigated in both wet and dry seasons above a rubber tree (Hevea brasiliensis)/secondary tropical forest in the Yunnan province of southwestern China. Drought conditions were unusually high during the dry season experiment. The eddy covariance measurement technique was used to measure isoprene fluxes, while monoterpene fluxes were modeled based on leaf level emission measurements. Maximum observed isoprene fluxes occurred during the wet season and daytim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 31 publications
3
48
0
Order By: Relevance
“…This is consistent with other studies in the tropics . It is possible that isoprene emissions increase during the dry season due to higher cumulative radiation exposure as observed by Sharkey et al (1999), Geron et al (2000), and Pe´tron et al (2001), although the cooler nighttime temperatures observed during the dry season at this site (Baker et al, 2005) have been found to reduce isoprene emission potential in these same studies.…”
Section: Article In Pressmentioning
confidence: 63%
See 2 more Smart Citations
“…This is consistent with other studies in the tropics . It is possible that isoprene emissions increase during the dry season due to higher cumulative radiation exposure as observed by Sharkey et al (1999), Geron et al (2000), and Pe´tron et al (2001), although the cooler nighttime temperatures observed during the dry season at this site (Baker et al, 2005) have been found to reduce isoprene emission potential in these same studies.…”
Section: Article In Pressmentioning
confidence: 63%
“…In 1983 Hevea plantations occupied 50,200 ha in Xishuangbanna Prefecture, or 2.6% of the total land area. This increased to 118,000 ha (6.2%) in 2000, and further increased to 170,000 (9.0%) ha by 2003 (Baker et al, 2005). Baker et al (2005) estimates that typical wet season daytime average monoterpene fluxes from H. brasiliensis plantations are approximately 10 times higher (2.0 vs. 0.2 mg C m À2 h À1 ) than typical mixed tropical forest (or non-forest) landscapes.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…Baker et al (2005) have recently demonstrated that monoterpene emissions from subtropical Chinese vegetation can be light-dependent but it is not known if this behavior is widespread in China. We have used Eq.…”
Section: Monoterpenesmentioning
confidence: 99%
“…However, the emission inventory described by that study does not include biogenic emissions. There are a few measurements of biogenic VOC emissions, including grasslands in northern China (He et al, 2004), and tropical forest in southern China (Wang et al, 2005a, b;Baker et al, 2005;Geron et al, 2006). To fully understand the chemistry in China and to model the distributions of air pollutants, the biogenic emissions of VOCs and NO need to be estimated.…”
Section: Introductionmentioning
confidence: 99%